Rolul Programului Sibiu 2007 – Capitală Culturală Europeană în dezvoltarea socioeconomică urbană - Luca, Sabina-Adina (Calitatea Vieții, 2009)
One of the cultural policies which had a great impact at the local and national level was the Program Sibiu 2007 – Cultural European Capital. This Program increased the visibility of Sibiu and Romania in the world, and some social and economic parameters of Sibiu. We based this statement on the impact which the Program had on the local economic agents, on the increase of the profitability rate and on the modernizations in the urban structure. Another benefit of this Program could be the possibility for another cultural capitals from Romania to use the experience which Sibiu gathered. At the some time, some useful comparisons, from different perspectives can be made between Sibiu and other cultural european capitals.